Understanding scientific collaboration in the research life cycle: Bio‐ and nanoscientists' motivations, information‐sharing and communication practices, and barriers to collaboration. (5th May 2015) - Chung, EunKyung; Kwon, Nahyun; Lee, Jungyeoun
Abstract : This study aims to identify the way researchers collaborate with other researchers in the course of the scientific research life cycle and provide information to the designers of e‐Science and e‐Research implementations. On the basis of in‐depth interviews with and on‐site observations of 24 scientists and a follow‐up focus group interview in the field of bioscience/nanoscience and technology in Korea, we examined scientific collaboration using the framework of the scientific research life cycle. We attempt to explain the major motivations, characteristics of communication and information sharing, and barriers associated with scientists' research collaboration practices throughout the research life cycle. The findings identify several notable phenomena including motivating factors, the timing of collaboration formation, partner selection, communication methods, information‐sharing practices, and barriers at each phase of the life cycle. We find that specific motivations were related to specific phases. The formation of collaboration was observed throughout the entire process, not only in the beginning phase of the cycle. For communication and information‐sharing practices, scientists continue to favor traditional means of communication for security reasons. Barriers to collaboration throughout the phases included different priorities, competitive tensions, and a hierarchical culture among collaborators, whereas credit sharing was a barrier in the research product phase.